2005
DOI: 10.1213/01.ane.0000156567.24800.0b
|View full text |Cite
|
Sign up to set email alerts
|

Errors and Omissions in Anesthesia: A Pilot Study Using a Pilot???s Checklist

Abstract: There are recent concerns that anesthesiologists are becoming less skilled in providing general anesthesia for Cesarean delivery. We considered whether a verbal checklist would help in the preparation for this event. We created a list of items to be checked when preparing to administer general anesthesia for a Cesarean delivery using expert opinion. This list was loaded onto an electronic checklist system with voice prompts and tested on 20 anesthesiologists using a high-fidelity anesthesia simulator. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 9 publications
1
63
0
7
Order By: Relevance
“…Another study conducted by Hart and Owen [27] in the anesthesia field demonstrated the function of a checklist as a memory aid tool. This study investigated the possibility of using a verbal checklist to assist the anesthesiologist administering general anesthesia during cesarean delivery.…”
Section: Checklist Use In the Operating Roommentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by Hart and Owen [27] in the anesthesia field demonstrated the function of a checklist as a memory aid tool. This study investigated the possibility of using a verbal checklist to assist the anesthesiologist administering general anesthesia during cesarean delivery.…”
Section: Checklist Use In the Operating Roommentioning
confidence: 99%
“…The problem with electronic checklists lies with the technology used to build the interface device. In the study by Hart and Owen [27], several subjects had difficulty understanding the voice synthesized by the device, so the written checklist was preferred to the verbal checklist.…”
Section: Checklist Use In the Operating Roommentioning
confidence: 99%
“…1,2,[9][10][11][12][13][14][15][16] General acceptance of the need for checklist-guided care in obstetrics has been slower, and largely limited to the past few years. Most efforts have been modeled after the groundbreaking programs developed by the Hospital Corporation of America to standardize the monitoring and administration of oxytocin, misoprostol, and magnesium sulfate, and the documentation of the management of shoulder dystocia.…”
mentioning
confidence: 99%
“…The results of these studies showed that participants were generally very positive about their training, and they perceived their training as contributing to safe practice. [38][39][40][41][42][43][44] However, a few studies also showed that this form of education was intimidating and stressful for participants, 41 and only a minority (*30%) believed it had influenced their clinical practice. 45,46 Interestingly, there is also a growing body of evidence showing that self-reports of participants do not predict their actual levels of performance.…”
Section: Changes In Learner Perceptionsmentioning
confidence: 99%